Success Rate of Root Canal Treatment by Conventional Root Canal Therapy Without Using Intracanal Medicament in Infected Canals (BIRDEM Medical Journal, 2017)
Background: Root canal system, when becomes infected is managed by thorough debridement and specific shaping of the root canal. It is to be followed by a specific type of filling. The ultimate goal of these approaches is to create an environment in which the bodys immune system can produce healing of the apical periodontal attachment apparatus. Thorough debridement and shaping are carried out usually by biomechanical preparation of root canal system along with intracranial medicament. The use of intracanal medicaments is still debatable. This study was designed to evaluate the usefulness of root canal treatment without using any biomedical preparation.Methods: The study was carried out in the Department of Conservative Dentistry and Endodontics, BSMMU, Dhaka July 2003 to July 2004. In the present study, 36 cases of endodontically involved infected teeth were treated by conventional root canal treatment without using intracanal medicaments and patients were followed up at 6 and 12 months after root canal treatment.Results: At 6 and 12 months follow up, an overall treatment success was revealed in clinical and radiological findings.Conclusion: It is the biomechanical preparation of the canal which decides the success rate of root canal treatment of infected teeth, not the use or nonuse of intracanal medicament.Birdem Med J 2017; 7(3): 221-223